2015
DOI: 10.1103/physreve.92.043102
|View full text |Cite
|
Sign up to set email alerts
|

Shock ion acceleration by an ultrashort circularly polarized laser pulse via relativistic transparency in an exploded target

Abstract: We investigated ion acceleration by an electrostatic shock in an exploded target irradiated by an ultrashort, circularly polarized laser pulse by means of one-and three-dimensional particle-in-cell simulations. We discovered that the laser field penetrating via relativistic transparency (RT) rapidly heated the upstream electron plasma to enable the formation of a high-speed electrostatic shock. Owing to the RT-based rapid heating and the fast compression of the initial density spike by a circularly polarized p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Second, in a dense enough plasma, the front-side ions are pushed by the 'laser piston', i.e., the space-charge field resulting from the laser ponderomotive force on the electrons. Third, under specific conditions, the laser piston or the electron pressure gradients created in an inhomogeneous plasma can launch a collisionless electrostatic shock [67][68][69][70], accelerating a fraction of the background ions to energies possibly larger than through TNSA [60,[71][72][73][74]. Further, for tightly focused lasers, ion acceleration can proceed via the electric field induced by magnetic vortices moving down density gradients [75,76].…”
Section: Introductionmentioning
confidence: 99%
“…Second, in a dense enough plasma, the front-side ions are pushed by the 'laser piston', i.e., the space-charge field resulting from the laser ponderomotive force on the electrons. Third, under specific conditions, the laser piston or the electron pressure gradients created in an inhomogeneous plasma can launch a collisionless electrostatic shock [67][68][69][70], accelerating a fraction of the background ions to energies possibly larger than through TNSA [60,[71][72][73][74]. Further, for tightly focused lasers, ion acceleration can proceed via the electric field induced by magnetic vortices moving down density gradients [75,76].…”
Section: Introductionmentioning
confidence: 99%
“…For 2D PIC simulation, we used our in-house code, cplPIC, which has been verified for numerous applications of laser-plasmas. [25][26][27][28][29] The cplPIC code employs the standard Yee-mesh-based field solver, 30 Villasenor-Buneman charge-conserving scheme for current calculation, 31 and Boris mover for particle motion. 32 For field ionization of neutral particles by the laser field, we used the barrier-suppression ionization (BSI) model 33 for electric field larger than the critical field EðtÞ > E crit and ADK (Ammosov-Delone-Krainov) tunneling ionization model, 34 otherwise : The critical electric field is given by 35…”
Section: Simulation Setupmentioning
confidence: 99%
“…Another necessary condition is a fast-enough hole-boring speed to match the sound speed, so the compressed density layer from the hole-boring process is converted into the shock eventually. Previously, we revealed that the relativistically transmitting pulse energy is the major heating source in CP-driven shock [21]. In low-initial-density plasma, the transmittance is high and so is the sound speed.…”
Section: -2mentioning
confidence: 99%
“…Previously, we suggested using the relativistic transparency for shock generation by circularly polarized (CP) pulses [21], where hot-electron recirculation is not available. Regarding the effects of transmittance on shock formation, there have been seemingly contradictory results; Zhang et al could obtain a quasimonoenergetic carbon beam of ∼7.5 MeV from an * mshur@unist.ac.kr opaque plasma irradiated by an LP pulse but could not do so in transparent plasma [22].…”
Section: Introductionmentioning
confidence: 99%